Management controversies : the unmotivated employee ([S.l.] : Ash Quary Productions)
Psychologist Eve Ash and Peter Quarry have a lively debate about how to deal with an employee who is bored and disinterested in their job
Psychologist, Eve Ash, Peter Quarry
Keywords: Problem employees; Labor discipline; Personnel management